'I enjoyed it because … you could do whatever you wanted and be creative': three principles for participatory research and pedagogy. Issue 4 (8th August 2018) - Flewitt, Rosie; Jones, Phil; Potter, John; Domingo, Myrrh; Collins, Paul; Munday, Ellie; Stenning, Karen
ABSTRACT: The complexity of many children's lives can result in their ideas being neither understood nor included in mainstream opportunities for learning, particularly children who are living with disadvantage. With a focus on developing ethical and inclusive principles for participatory research and pedagogy, this paper reports on a pilot project where we worked with young, hard-to-reach individuals across four sites in England to enable them to design and carry out research about their experiences and views of disadvantage. Here, we present snapshots of the young participants' choices of research topics and methods, which reflected their own lives and interests, and led to powerful visualizations of the complexity of child and youth disadvantage. Reflecting back on the project, we discuss effective ways to initiate and sustain participatory research that can enable young researchers to be involved as active and empowered agents at every stage of the research process. We also consider the implications for developing participatory pedagogy, with researchers working alongside educators to create school cultures that foster belonging and genuinely support all students' expertise and ways of knowing by looking beyond the school buildings and into their lives in the wider community.